Analysing Higher Educational Institutions' Role in Fulfilling their Third Mission - Odei, Samuel Amponsah; Anderson, Henry Junior (My University, 2021)
The transitional process happening in higher educational institutions tend to underscore initiatives aimed at positioning these institutions as hubs of knowledge production and transfers capable of influencing regional development. Nonetheless, the literature has failed to capture the extent to which these institutions have embraced their third mission of impacting regional development, thus calling for a broader range of approaches in examining the roles of these institutions. To fill this gap, this study evaluates the various ways higher educational institutions have embraced their third mission of contributing to the development management activities of regions. We sourced data from 164 higher education institutions (HEIs) located across the United Kingdom, employing the propensity score matching estimation model to estimate the average treatment effects (ATE) of various interventions. The results demonstrate additionality effects of HEIs on graduate support, attracting inward investment, R&D collaborations and network facilitation. Surprisingly, our results show HEIs as playing an insignificant role in supporting SMEs, and knowledge exchanges. The main implication of this is that adopting initiatives that proved successful in specific universities to other higher educational settings remains a challenge.
Analýza úlohy vysokých škol při plnění jejich třetí role
Keywords: higher education insti-tutions; knowledge transfers; propensity scores matching; regional development; third mission; United Kingdom; vysokoškolské instituce; transfer znalostí; regionální rozvoj; třetí role; Spojené království